Types of grammatical and lexical errors made by students with a mild intellectual disability at the second stage of their education a qualitative analysis - Marciniak-Firadza, Renata (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
The aim of the article is to provide a qualitative description of the errors committed by pupils with mild intellectual disabilities. The discussed issue has not yet been the subject of a scientific description from a linguistic point of view. The analysis of errors was based on Andrzej Markowski's classification with small additions from Zygmunt Saloni’s classification. Due to the volumetric framework, the article is limited to discussing grammatical and lexical errors. The research showed that pupils with mild intellectual disabilities make similar errors as those with typical development. No qualitative differences were noted between the study group and the control group, only quantitative ones.